Pendekatan Misi Joseph Kam di Tanah Maluku Sebuah Integrasi Sejarah dan Praktik dalam Teologi Penginjilan - Yusep Arimatea; Martha Mulyani Kurniawan (STIKAS Santo Yohanes Salib Kalimantan Barat, 2025)
This study aims to analyze the mission methodology applied by Joseph Kam in evangelizing Maluku in the 19th century. Using a practical historical approach, this study explores the strategies used by Joseph Kam, such as home visits, health services, education, and Bible translation, and how these methods were adapted to the local cultural context. This research method involves literature studies and analysis of relevant historical sources to describe the social and religious context at that time. The main findings of this study indicate that Joseph Kam's mission methodology is highly contextual and effective in reaching the Maluku community, and has had a long-term impact on the development of the church in the region. This study also highlights the relevance of Joseph Kam's methods for contemporary evangelism, especially in terms of a sensitive approach to local culture.